Enhancing Critical Thinking Through Responding to The English Poetry - Isti Kristiani (Journal of English Education Program (JEEP), 2016)
Critical thinking in learning is very important because the skill of critical thinking can influence understanding, analyzing, evaluating arguments and viewpoint (Gregory, William, Henry and James 2011, p. 27). An active maker-or meaning in the experience or responding to a text, that brings meaning to and taking meaning from a symbolic form (Vandergrift 1990, p. 127). The study employed a case study design. The writer took the second year in D class that consisted of 18 students which is divided into 6 group and only 12 students were given questionnaire. In determining the sample, the writer used cluster sampling technique. The data were obtained from several sources, including a observation and questionnaire to students. The findings shows that from each group of basic critical thinking which consist of 6 group, half of group included in category, the dominant category from it was fairness category which total 5 from 6 group. Keywords: Poetry, Critical thinking, literature in EFL classroom